2017
DOI: 10.3390/su9081327
|View full text |Cite
|
Sign up to set email alerts
|

How Is Environmental Proactivity Accomplished? Drivers and Barriers in Firms’ Pro-Environmental Change Process

Abstract: Abstract:The contaminating effects of economic activity and the scarcity of natural resources has led firms to a situation in which corporate strategy has been compromised by environmental issues. The objective of this paper is to analyse some of the factors determining the pro-environmental change process by considering the drivers encouraging firms to progress in environmental protection and the barriers that curb this progress. Using a structural equation model implemented on a sample of 303 firms, our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 89 publications
4
16
0
3
Order By: Relevance
“…Environmental collaboration (Horbach et al, 2012;Wagner, 2007), green skills (Cainelli, Mazzanti, & Montresor, 2012), market pressure (Nesta, Vona, & Nicolli, 2014;Ziegler & Rennings, 2004), and export behavior (Christmann & Taylor, 2001; Lanoie, Laurent-Lucchetti, Johnstone, & Ambec, 2011) are positively and directly related to EI. However, scholars have often argued that there was an intermediate driver that mediated these relationships (see, e.g., Del Río, Carrillo-Hermosilla, et al, 2016, Valero-Gil et al, 2017, and this is also suggested by our interviewees, who confirmed that these EI drivers congregated the resources and capabilities of the firms via environmental strategies to promote EI. 4 Thus, because environmental strategy is a key variable that mediates the relationship between different drivers and EI, the focus in this paper is precisely on such mediating role.…”
Section: Indirect Effects On Ei Through Environmental Strategysupporting
confidence: 80%
“…Environmental collaboration (Horbach et al, 2012;Wagner, 2007), green skills (Cainelli, Mazzanti, & Montresor, 2012), market pressure (Nesta, Vona, & Nicolli, 2014;Ziegler & Rennings, 2004), and export behavior (Christmann & Taylor, 2001; Lanoie, Laurent-Lucchetti, Johnstone, & Ambec, 2011) are positively and directly related to EI. However, scholars have often argued that there was an intermediate driver that mediated these relationships (see, e.g., Del Río, Carrillo-Hermosilla, et al, 2016, Valero-Gil et al, 2017, and this is also suggested by our interviewees, who confirmed that these EI drivers congregated the resources and capabilities of the firms via environmental strategies to promote EI. 4 Thus, because environmental strategy is a key variable that mediates the relationship between different drivers and EI, the focus in this paper is precisely on such mediating role.…”
Section: Indirect Effects On Ei Through Environmental Strategysupporting
confidence: 80%
“…Interestingly, top management commitment in SMEs, in the opinion of Rasi et al (2014), has an effect only on the improvement of environmental organizational and management practices. However, there is some evidence that the motivation, positive attitude and engagement of top management in large enterprises, as well as owners in SMEs towards environmental protection, are the key factors in implementing PES (Jansson, Nilsson, Modig, & Hed Vall, 2017; Sharma & Sharma, 2011; Valero‐Gil, Rivera‐Torres, & Garcés‐Ayerbe, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, absorptive capability, product innovation, and green image are external stakeholder oriented, whereas transformative capability, process innovation, and competitive advantage are internal stakeholder oriented. Making differences in resource utilization and transformation, environmental proactivity is likely to moderate the aforementioned relationships [59,60].…”
Section: Research Modelmentioning
confidence: 99%